Peran Pemerintah Daerah dalam Memanfaatkan Media Sosial untuk Informasi Potensi Wisata Danau Rana Mese di Desa Golo Loni - Marco Adesaputra Sanjaya Nule; Petrus Kase; Theny I. B. Kurniati Pah (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This study aims to analyze the role of the local government in utilizing social media as an information medium for the tourism potential of Rana Mese lake in East Manggarai Regency. The research employs a qualitative descriptive approach with data collected through interviews, observation, and documentation. Informants were selected using purposive sampling, consisting of government officials, tourism managers, local communities, and tourists. Data analysis follows the model of Miles and Huberman, including data reduction, data display, and conclusion drawing, while data validity is ensured through triangulation techniques. The results indicate that the local government has performed strategic roles as promoter, informant, motivator, and facilitator in utilizing social media for tourism development. Social media has contributed to increasing destination visibility, tourist visits, and local economic activities. However, the implementation is not yet optimal due to several constraints, such as limited internet access (blank spot areas), low digital literacy among communities, and limited inter-institutional coordination. Additionally, tourism management involves multiple stakeholders, including BKSDA as the primary conservation authority, which emphasizes environmental protection alongside tourism promotion. The study concludes that strengthening digital infrastructure, improving community capacity, and enhancing inter-agency coordination are essential to optimize the use of social media in supporting sustainable tourism development.